Competitive size asymmetry, not intensity, is linked to species loss and gain in a native grassland community. Issue 6 (11th April 2022) - Brown, Charlotte; Cahill, James F.
Abstract: Competition is often highlighted as a major force influencing plant species diversity. However, there are multiple facets of competition (e.g., strength, intransitivity, and size asymmetry) that may have independent and differential impacts on diversity, making understanding the degree to which competition structures communities difficult. Unfortunately, field‐based experiments that decouple multiple facets of competition are lacking, limiting our ability to test theoretical frameworks and reducing understanding of the actual linkages among competition and coexistence. Here, we experimentally manipulate the size structure of local grassland communities to examine the relative impacts of competitive size asymmetry (i.e., competitive advantage based on relative size) and intensity (i.e., mean effect of neighbors on plant growth) on species loss and gain. Increased competitive size asymmetry was associated with increased species loss and decreased species gain, while no relationship was found between competitive intensity and species loss and gain. Furthermore, the probability of loss was not dependent on a species initial size, suggesting that small species may not always be the losers of size‐asymmetric interactions. Instead, loss was dependent on species rarity, where loss was higher for rare species. Overall, these results suggest that competitive size asymmetry may be more important for species loss than intensity in some plant communities and demonstrates the importance of decoupling different aspects of competition to better understand their drivers and ecological consequences.